Market efficiency in Singapore : a study on the impact of crisis and nature of company. - Chan, Guan Ting. (2012)
The purpose of this research is to examine the informational efficiency of the Singapore Stock Market during crisis and non-crisis periods and between local and foreign companies. This will help stock market participants better understand how stocks of different companies behave when earnings announcements of different nature are made. The Straits Times Index (STI) is adopted as the proxy for examining the efficiency of the Singapore Stock Market. Our study adopts the event study methodology, by separating the period of each earnings announcement to three different windows, namely pre-announcement period, announcement period and post-announcement period. Daily closing share prices were used to calculate the cumulative abnormal returns (CARs), so as to determine the type of earnings announcements. The market reactions are then used to examine the efficiency of the market. Our results show that there is market over-reaction and slight drift in post announcement periods especially during crisis periods. The nature of companies also plays a part in the efficiency of the market. Local companies with purportedly better corporate governance show less variability in share prices as compared to foreign companies of the STI. In view of this market anomaly, we recommend timelier reporting of material information for all listed companies. In addition, unsophisticated stock market participants are encouraged to adopt a passive strategy by holding a diversified portfolio of investments, since speculating in times of crisis do not guarantee good returns and increases the risk of losses due to higher share price fluctuations.